2013
DOI: 10.1212/wnl.0b013e318297eecf
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury may be an independent risk factor for stroke

Abstract: In this large cohort, TBI is associated with ischemic stroke, independent of other major predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
106
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 32 publications
12
106
1
Order By: Relevance
“…TBI is not currently identifi ed as a risk factor for stroke. However, one trauma database found that 37% of trauma patients are admitted secondary to TBI and, in a 2½-year follow-up period, patients who suff ered a TBI had a 31% increased risk of being hospitalized secondary to ischemic stroke over non-TBI trauma patients ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…TBI is not currently identifi ed as a risk factor for stroke. However, one trauma database found that 37% of trauma patients are admitted secondary to TBI and, in a 2½-year follow-up period, patients who suff ered a TBI had a 31% increased risk of being hospitalized secondary to ischemic stroke over non-TBI trauma patients ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…[15] This is, especially, a matter of concern in patients with severe and critical TBI with GCS≤8 and DAI, since, pre-hospital neurologic deterioration and lower level of consciousness are independent factors of poor prognosis. [16,17] Severe traumatic brain injury is an isolated predisposing factor for succeeding posttraumatic cerebral infarction (PTCI); [18,19] in this setting, besides acute reperfusion strategies such as thrombolysis or mechanical clot removal, practically all available therapeutic protocols focus on palliation and use of neuroprotective agents for mitigation of secondary damage to the nervous system. Citicoline has been reported to have protective and restorative effects on the central nervous system (CNS) by inducing Na + /K + ATPase activity, decreasing lipid peroxidation, preserving mitochondrial membrane cardiolipin, suppressing phospholipase A 2 activity, improving neuroplasticity and synthesis of neurotransmitters like acetylcholine (Ach) or dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that TBI is associated with increased risk of stroke [10][11][12]. Although the actual mechanism is still not completely understood, several hypotheses have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in several studies TBI was found to be associated with increased risk of [10][11][12]. Because stroke results from disturbance of the blood supply to the brain, it has been hypothesized that vascular damage from TBI may also induce stroke in survivors [11].…”
Section: Introductionmentioning
confidence: 99%